Descripción de la posible asociación entre cuatro competencias directivas y el cumplimiento de los indicadores de gestión de cinco gerentes de la empresa Geotecnia & Cimentaciones G&C - Carmona Donoso, Vanessa; Cubillos Vargas, Yuliana (Universidad Antonio Nariño, 2024)
The present research seeks to determine the possible association between four managerial competencies and the fulfillment of the management indicators of five managers of the company Geotecnia & Cimentaciones, in Bogotá city. For this purpose, a quantitative-descriptive analysis was performed on a sample of 5 managers made up of four women in a range of 31 and 51 years of age and a 36-year-old man, Civil Engineering and specializations in finance, Organizational and occupational psychology and master's degree in geotechnics, respectively. For this measurement was used the Competence Assessment (COMPE-TEA), proposed by David Arribas and Jaime Pereña (2009).